Retensi Kognitif Biologi Siswa Sekolah Menengah Atas pada Pembelajaran Kooperatif Jigsaw - Azizah, Aulia; Bahri, Arsad; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2020)
Abstract.Â Conventional learning model with lecture method that teacher- centered was still dominating and usually used by teacher in learning proccess at high school. Teacher needed learning model that can increase student cognitive retention. This research aims to determine whether there is influence of the cooperative learning Jigsaw-type model on retention of cognitive. The design is Pretest-Posttest Control Group Design. The population in this study were all students of class X MIPA SMA Negeri 5 Wajo which consisted of 3 classes. The research sample was selected by random sampling technique, namely X MIPA 2 as an experimental group with 23 students and X MIPA 3 as a control group with 26 students. Data collected by using a multiple choice test totaling 20 numbers. The collected research was analyzed using descriptive statistics and inferential statistics. The results showed that there was an effect of the application of the cooperative learning Jigsaw-type model on retention of cognitive of students in SMA Negeri 5 Wajo. Teacher can use this model in other lectures considere with the material characteristic.Â Keywords:Â Jigsaw-type, Retention of Cognitive, Biology Learning